Theory and practice of simulation of optical tweezers. (July 2017) - Bui, Ann A.M.; Stilgoe, Alexander B.; Lenton, Isaac C.D.; Gibson, Lachlan J.; Kashchuk, Anatolii V.; Zhang, Shu; Rubinsztein-Dunlop, Halina; Nieminen, Timo A.
Abstract: Computational modelling has made many useful contributions to the field of optical tweezers. One aspect in which it can be applied is the simulation of the dynamics of particles in optical tweezers. This can be useful for systems with many degrees of freedom, and for the simulation of experiments. While modelling of the optical force is a prerequisite for simulation of the motion of particles in optical traps, non-optical forces must also be included; the most important are usually Brownian motion and viscous drag. We discuss some applications and examples of such simulations. We review the theory and practical principles of simulation of optical tweezers, including the choice of method of calculation of optical force, numerical solution of the equations of motion of the particle, and finish with a discussion of a range of open problems. Abstract : Highlights: The theory of simulation of optical tweezers is reviewed. Practical principles are discussed. Open questions are discussed.